Have Sweet Potato.... Keep vitamin A deficiency far away - Pati, kalidas (Indian Horticulture, 2019)
Orange-fleshed sweet potato contain heigher total carotenoids and carotene contain than white and cream fleshed ones. Carotenoids in orande-fleshed sweet potato is heighly vitamin A active.